Pension System Future Direction on Employees of SMEs in Indonesia, Vietnam, and Hungary - Hadi, Abdul; Ngo, Duong Minh; Bruder, Emese; Badriah, (Acta Carolus Robertus, 2023)
Small and medium-sized enterprises are extremely important to the economy. However, businesses in this sector and their employees need help to obtain social security. Hungary, Indonesia, and Vietnam are nations in various geographical locations with obvious disparities in ethnography and pension system structure. Meanwhile, the proportion of SMEs in all three countries is comparable, accounting for a large fraction of the estimated enterprises that play important roles in the national economy. As a result, this research analyzes the pension system and the present condition of pension schemes for SMEs in Hungary, Indonesia, and Vietnam. In this paper, the researchers conducted a literature review. According to the comparison of the three nations, there are various barriers in the SME sector in accomplishing employee pension schemes: limited financial resources, employees who do not perceive immediate benefits and are not risk-averse, low awareness of current pension schemes, the expense of social contributions and increased in the minimum wage, both employers and employees negotiate to stop social insurance payments, a high job turnover rate, and employees are more likely to earn prepaid social insurance payments to assist them in making ends meet. Hungary, Indonesia, and Vietnam's governments should make participation mandatory for people working in SMEs, actively publicize the importance of pension schemes to SME employees, simplify registration and payment of pension contributions through digital channels, incentivize SMEs to participate in pension systems, and enact legislation against SMEs and their employees to encourage participation.